HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PEMANFAATAN BUKU KIA TERHADAP IBU HAMIL DALAM PENGENALAN TANDA BAHAYA KEHAMILAN DI POSKESDES SARIGADUNG KABUPATEN TANAH BUMBU - Gusrinawati, Fatma; Dewi , Vonny Khresna; Megawati, Megawati; Hipni, Rubiati (Cahaya Ilmu Bangsa Institute, 2025)
The number of pregnant women targeted at Simpang Empat Care Health Center in 2024 is 1,046, but only 762 have Maternal and Child Health (MCH) books due to the perception that the MCH book is merely a health record for healthcare workers, hindering the development of health behaviors among pregnant women. This study aims to determine the relationship between knowledge and attitudes toward the utilization of MCH books in recognizing pregnancy danger signs at Sarigadung Village Health Post in 2024. The study employed a quantitative design with a cross-sectional approach involving 66 pregnant women selected through random sampling. Independent variables included knowledge and attitudes, while the dependent variable was the utilization of the MCH book. A questionnaire was used as the research instrument, and data analysis was performed using the chi-square test. The results showed that 34 respondents (51.5%) had good knowledge, 22 (33.3%) had moderate knowledge, and 10 (15.2%) had poor knowledge; 49 respondents (74.2%) had positive attitudes, and 17 (25.8%) had negative attitudes. The chi-square test demonstrated a significant relationship between knowledge (p-value 0.000) and attitudes (p-value 0.000) with the utilization of MCH books. In conclusion, the utilization of MCH books in recognizing pregnancy danger signs is associated with pregnant women's knowledge and attitudes Jumlah sasaran ibu hamil di Puskesmas Perawatan Simpang Empat tahun 2024 mencapai 1.046 orang, namun hanya 762 orang yang memiliki buku KIA karena anggapan bahwa buku KIA hanya sebagai pencatatan kesehatan bagi petugas, sehingga menghambat pembentukan perilaku kesehatan ibu hamil. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan sikap dengan pemanfaatan buku KIA dalam pengenalan tanda bahaya kehamilan di Poskesdes Sarigadung tahun 2024. Penelitian menggunakan desain kuantitatif dengan pendekatan cross-sectional pada 66 ibu hamil yang dipilih secara random sampling. Variabel independen meliputi pengetahuan dan sikap, sedangkan variabel dependen adalah pemanfaatan buku KIA. Instrumen yang digunakan berupa kuesioner, dengan analisis data menggunakan uji chi-square. Hasil penelitian menunjukkan bahwa 34 responden (51,5%) memiliki pengetahuan baik, 22 (33,3%) cukup, dan 10 (15,2%) kurang; 49 responden (74,2%) memiliki sikap positif, dan 17 (25,8%) negatif. Uji chi-square menunjukkan hubungan signifikan antara pengetahuan (p-value 0,000) dan sikap (p-value 0,000) dengan pemanfaatan buku KIA. Kesimpulannya, pemanfaatan buku KIA dalam pengenalan tanda bahaya kehamilan berhubungan dengan pengetahuan dan sikap ibu hamil